2016
DOI: 10.1007/s12011-016-0666-7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anticancer Activity of Au, Ag Nanoparticles Synthesized Using Commelina nudiflora L. Aqueous Extract Against HCT-116 Colon Cancer Cells

Abstract: Recently, metal nanoparticles have been getting great medical and social interests due to their potential physico-chemical properties such as higher affinity, low molecular weight, and larger surface area. The biosynthesized gold and silver nanoparticles are spherical, triangular in shape with an average size of 24-150 nm as reported in our earlier studies. The biological properties of synthesized gold and silver nanoparticles are demonstrated in this paper. The different in vitro assays such as MTT, flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 30 publications
8
67
0
1
Order By: Relevance
“…IC 50 of AgNps-CN towards HSC-4 cell lines was 1.61 ± 0.14 mg/mL. Recently, Palaniselvam et al (2015) suggested when HCT-116 treated with silver nanoparticles, percentage viability of cells affected and showed 50% cell death at 50 mg/mL [7]. Study by Sankar et al, (2013) reported anticancer effects of silver nanoparticle against human lung cancer cell lines (A549) with 50% of cell death at 100 mg/mL [22].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…IC 50 of AgNps-CN towards HSC-4 cell lines was 1.61 ± 0.14 mg/mL. Recently, Palaniselvam et al (2015) suggested when HCT-116 treated with silver nanoparticles, percentage viability of cells affected and showed 50% cell death at 50 mg/mL [7]. Study by Sankar et al, (2013) reported anticancer effects of silver nanoparticle against human lung cancer cell lines (A549) with 50% of cell death at 100 mg/mL [22].…”
Section: Discussionmentioning
confidence: 96%
“…There are several studies reported phenolic compounds of the extract may enhance anticancer properties of silver nanoparticles. For example, silver nanoparticles synthesized by Commelina nudiflora caused cytotoxic activity towards human colon cancer cell lines [7]. Besides that, it increased the expression of caspase-3, caspase-8 and caspase-9 which involved in apoptosis mechanism [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same manner, Rejeeth et al 57 reported that the green-based synthesis of silver nanoscale molecule induced in vitro proliferation inhibition on the breast cancer cell. Also, Kuppusamy et al 58 investigated that the biosynthesized AgNPs using the aqueous extract of Commelina nudiflora L increased cytotoxicity and significantly reduced cell viability of colon cancer cells. Biofunctional silver nanoparticles synthesized within various plant extracts of clove and guava evidenced the satisfying anti-cancer impact versus four different human cancer cell lines; colorectal adenocarcinoma, kidney, chronic myelogenous, leukemia, bone marrow, and cervix.…”
Section: Effects Of Agnps and Cefotaxime-cs-agnps On Mcf-7 Breast Canmentioning
confidence: 99%
“…Plant extract synthesized silver nanoparticles (AgNPs) have been shown to possess better antimicrobial activities against a wide range of microorganisms including multidrug resistant bacteria and yeast pathogens 1 . AgNPs have been shown to be effective against a broad range of human cancers such as lung, cervical, breast, and colon cancer because the water-soluble organic moieties in the nanoparticles induce a synergistic antiproliferative effect in various cancer cell lines, and thus have proven useful in various types of cancer treatments [2][3][4][5][6] . AgNPs have been found to induce the apoptotic pathway in vitro through free oxygen radical generation, which has antitumor, antiproliferative and antiangiogenic effects in vitro 7 .…”
Section: Introductionmentioning
confidence: 99%